The Impact of Electronic Money on the Efficiency of the Payment System and the Substitution of Cash in Indonesia - Alghifari Mahdi Igamo; Telisa Aulia Falianty (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2018)
This paper examines the effect of electronic money on the efficiency of the payment system and narrow money demand function from 2007-2017 using Indonesia monthly data. This reseacrh found that electronic money increase private consumption expenditures as a proxy of the efficiency. On the other hand, result showed that electronic money decrease narrow money (M1).